TONGKAT ALI PLANTS OF EURYCOMA LONGIFOLIA AND STEMA TUBEROSA STIMULATE SEXUAL AROUSAL IN DOMESTIC COCKS - Vejayan, Jaya; Che Yahya, Yasmin Amira; Chakravarthi, Srikumar; Bathmanathan, Rupbansraaj; Ibrahim, Halijah; Yun, Aida (Malaysian Journal of Science, 2020)
This study compared the aphrodisiac ability of Tongkat Ali Merah (red type) or Stema tuberosa to Tongkat Ali Putih (white type) or E. longifolia. Fowls dosed orally with capsule containing E. longifolia and S. tuberosa respectively for 30 days followed by determining the efficacy by evaluating their sexual mating behavior parameters, testosterone blood level and histology of testicular tissue. Safety parameters included biochemical levels and histology of the liver. Both types of Tongkat Ali shown increases in testosterone levels (7.7±0.59 nmol/L and 6.25±0.70 nmol/L and 4.08±0.85 nmol/L; E. longifolia, S. tuberosa and control fowls, respectively) as well as testicular histology showing seminiferous tubules with increased cellularity with no evidence of inflammation or fibrosis compared to the control to indicate as testosterone boosters. All biochemical parameters tested shown to be within the control values except for alanine aminotransferase of E. longifolia i.e. 23.50±6.36 u/L (control = 8.00±2.94 u/L). Additionally, some moderate tissue changes (focal areas of congestion of central vein and periportal scattered inflammation) were visible for the liver taken from E. longifolia treated fowls. S. tuberosa found without any untoward effects. Tongkat Ali Merah hereby been confirmed to boost testosterone in fowls although not as effective as Tongkat Ali Putih.